2020
DOI: 10.2174/1389201021666191216122555
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitogen-Activated Protein Kinases by Natural Products: A Novel Therapeutic Approach for Inflammatory Bowel Diseases

Abstract: : An increase in the prevalence of IBD as a multifactorial intestinal chronic inflammation as well as the absence of a certain cure, has created an innovative era in the management of IBD by molecule/pathway-based anti-inflammatory approaches. : There are credible documentations that demonstrate MAPK acts as IBD regulator. Upon the activation of MAPK signalling pathway, the transcription and expression of various encoding inflammatory molecules implicated in IBD are altered, thereby exacerbating the inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 119 publications
0
16
0
Order By: Relevance
“…IBD and other autoimmune diseases have also been linked to the NF-κB protein (7). MAPKs are composed of various serine and threonine kinases that induce inflammation (8). Other evidence suggests that inhibiting the NF-κB and MAPK signaling pathways is vital in IBD treatment (9).…”
Section: Introductionmentioning
confidence: 99%
“…IBD and other autoimmune diseases have also been linked to the NF-κB protein (7). MAPKs are composed of various serine and threonine kinases that induce inflammation (8). Other evidence suggests that inhibiting the NF-κB and MAPK signaling pathways is vital in IBD treatment (9).…”
Section: Introductionmentioning
confidence: 99%
“…After inflammatory factors activate the MAPK signaling pathway, the transcription and expression of inflammatory genes related to inflammatory bowel disease (IBD) are changed, which intensifies the development of inflammation. 44 In IBD model mice, the expression of MAPK1/3 increased significantly. However, its expression decreased after drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, based on the two aspects of network construction and central network evaluation, 26 key targets of the ZJP potential target network were selected which were significantly enriched in three UCrelated signaling pathways, including the PI3K-Akt signaling pathway, MAPK signaling pathway, and toll-like receptor signaling pathway. Studies have shown that the PI3K-Akt signaling pathway could regulate the inflammation and oxidative stress of UC [12,13]; the MAPK pathway played a key role in regulating the development of UC inflammation Evidence-Based Complementary and Alternative Medicine [14]; the toll-like receptor signaling pathway played an important role in the immune system and participated in the inflammatory process of UC [15]. However, the key target of this study enriched in the toll-like receptor signaling pathway was focused on the downstream MAPK pathway crosstalk.…”
Section: Discussionmentioning
confidence: 99%